“Giant” Arachnoid Granulations Just Like CSF?: NOT!! - Trimble, C.R.; Harnsberger, H.R.; Castillo, M.; Brant-Zawadzki, M.; Osborn, A.G. (American Journal of Neuroradiology, 2010)
SUMMARY: “Giant” AGs (>1 cm) are uncommon and can be misdiagnosed as venous sinus pathology such as a neoplasm or thrombosis. Seventeen patients with a total of 19 venous sinus AGs of >1 cm were collected from contributing authors. MR imaging was available for all AGs; CT, for 5/19; and DSA, for 7/19. Intra-AG fluid was compared with CSF in subarachnoid spaces. Nonfluid AG tissue was compared with gray matter. Diagnosis was based on imaging findings. Fluid within giant AGs did not follow CSF signal intensity on at least 1 MR image in nearly 80% (15/19) of AGs. Nine of these 15 AGs had CSF-incongruent signal intensity on ≥2 MR images. CSF-incongruent signal intensity was seen in 8/8 AGs on FLAIR, 7/10 on precontrast T1WI, 13/19 on T2WI, and 8/14 on contrast-enhanced T1WI. Nonfluid signal intensity was present in 18/19 AGs and varied from absent/hypointense (intra-AG flow voids) to gray matter isointense (stromal tissue). AGarachnoid granulationAVarachnoid villusCAQCertificate of Added QualificationCECTcontrast-enhanced CTCTVCT venographyDSAdigital subtraction angiographyDWIdiffusion-weighted imagingFLAIRfluid-attenuated inversion recoveryMRVMR venographySSSsuperior sagittal sinusT1WIT1-weighted imagingT2WIT2-weighted imagingTStransverse sinus